Lipid signaling and metabolism - Ntambi, James M. (Academic Press, 2020)
With recent technological advances and mass-scale sequencing approaches, our understanding of lipid metabolism and signaling, and its role in health and disease processes, has increased significantly. The maintenance of metabolic health has been shown to require complex regulation of metabolic processes in several tissues, and extensive crosstalk among tissues and organs. Lipids act not only as constituents of cellular membranes, but as key signaling mediators, serving new and unexpected biological, metabolic, and cellular functions.